Snake Bite Health Education on Community and Pre Hospital Handling - Yuly Peristiowati; Novita Ana Anggraini; Dedy Mochtar Setiaji; Hariyono (Universitas STRADA Indonesia, 2024)
Background: Snake bites are one of the most common health problems in tropical and subtropical countries. WHO has included snakebite in the list of neglected tropical diseases. The majority of Indonesians work in agriculture and are at high risk of being bitten by snakes. Pre-hospital handling of snakebites according to WHO recommendations by immobilizing using bandages and splints on the part affected by the snakebite then immediately refer to the nearest health service center.Purpose: This study aims to determine the effect of snakebite health education on people's knowledge and behavior about handling snakebites before going to the hospital in Wungu Village, Wungu District, Madiun Regency.Method: The research design is quasi-experimental with a one-group pre-test and post-test design. The population is the entire community of Wungu Village, Wungu District, Madiun Regency with a sample of 100 respondents by random sampling. Collecting data using a questionnaire analyzed with the Wilcoxon test.Results: The results of the research on community knowledge and behavior before being given health education were 44 people (88%) less knowledgeable and 39 people (78%), after being given health education, more than half of the respondents had good knowledge, namely 26 people (52% ) and many changes from good behavior as many as 29 people (58%).Conclusion: There is an effect of health education on people's knowledge and behavior about handling snake bites before going to the hospital with p = 0.000 <0.05.